2011
DOI: 10.1016/j.jjcc.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineralocorticoid receptor antagonist spironolactone on atrial conduction and remodeling in patients with heart failure

Abstract: Spironolactone improves atrial conduction and remodeling in patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…This effect is similar to previous findings (24)(25)(26). Although the current patients did not clinically present with symptoms of overt heart failure, the present findings suggest that eplerenone may help to prevent the future progression of heart failure in such patients.…”
Section: Discussionsupporting
confidence: 92%
“…This effect is similar to previous findings (24)(25)(26). Although the current patients did not clinically present with symptoms of overt heart failure, the present findings suggest that eplerenone may help to prevent the future progression of heart failure in such patients.…”
Section: Discussionsupporting
confidence: 92%
“…The primary search for clinical trials on MRAs and left ventricular dysfunction generated 559 potentially relevant articles, of which 19 met the selection criteria and were published between 1995 and 2011. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A flow diagram schematized the process of selecting and excluding articles with specific reasons (Figure 1). Five of 19 qualified trials recorded outcomes within >1 time point in treatment, yielding a total of 26 studies conducted exclusively in subgroup analyses by treatment durations.…”
Section: Eligible Trialsmentioning
confidence: 99%
“…Data are presented as mean ± standard deviation (SD). The sample size calculations were based on the previous studies about the effect of mineralocorticoid receptor antagonists and calcium channel blockers, which reported that the percent change in Ad after the administration of spironolactone and calcium channel blockers was 6% and 0%, respectively . Based on these data, assuming the SD of percent change in Ad of 6%, it was estimated that inclusion of 17 patients in each group allowed for a statistical power of 80% and a type I error rate of 0.05.…”
Section: Methodsmentioning
confidence: 99%